A comprehensive expression landscape of RNA-binding proteins (RBPs) across 16 human cancer types. Issue 2 (1st February 2020) - Zhang, Bin; Babu, Kamesh R.; Lim, Chun You; Kwok, Zhi Hao; Li, Jia; Zhou, Siqin; Yang, Henry; Tay, Yvonne
ABSTRACT: RNA-binding proteins (RBPs) are key regulators of posttranscriptional processes such as RNA maturation, localization, turnover and translation. Despite their dysregulation in various diseases including cancer, the landscape of RBP expression in human cancer has not been well elucidated. Here, we built a comprehensive expression landscape of 1504 RBPs across 16 human cancer types, which revealed that RBPs are predominantly upregulated in tumours and this phenomenon is affected by the tumour immune subtypes and microenvironment. Across different cancer types, 109 RBPs are consistently upregulated while 41 RBPs are consistently downregulated. These up-regulated and down-regulated RBPs show distinct molecular characteristics and prognostic effects, whereas their dysregulation is mediated by distinct cis/trans-regulatory mechanisms. Finally, we validated one candidate PABPC1L that might promote colon tumorigenesis by regulating mRNA splicing. In summary, we built a comprehensive expression landscape of RBPs across different cancer types and identified consistently dysregulated RBPs which could be novel targets for developing broad-spectrum anticancer agents.